2021
DOI: 10.1021/acsami.0c18942
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Linkage Between Structure, Electrochemical Properties, and Chemical Compositions of LiNi1–xyMnxCoyO2 Cathode Materials

Abstract: LiNi1–x–y Mn x Co y O2 (NMC) is an important class of high-energy-density cathode materials. The possibility of changing both x and y in the chemical formula provides numerous materials with diverse electrochemical and structural properties. It is highly desirable to have guidance on correlating NMC structural and electrochemical properties with their chemical composition for material designing and screening. Here, using synchrotron-based X-ray diffraction, X-ray absorption spectroscopy, electrochemical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 61 publications
4
9
0
Order By: Relevance
“…This change in this phase transition process that has a major contribution to the particle crack formation process is consistent with what was suggested in previous reports as the advantage of doping to Ni-rich NCMs. , A possible reason for the stabilization during this phase transition is the stronger Nb–O bonds. According to a recent study by Hu et al on the fundamental links between the spatial structure, electrochemical properties, and chemical composition of metal oxide cathodes, oxygen release is also a cause of surface phase changes and local stresses, which contribute to the formation of intergranular cracks . As Hu et al demonstrated in their study, our study shows a link between stronger oxygen binding (in our case via Nb–O bonds) and a reduced formation of intergranular cracks …”
Section: Resultssupporting
confidence: 70%
“…This change in this phase transition process that has a major contribution to the particle crack formation process is consistent with what was suggested in previous reports as the advantage of doping to Ni-rich NCMs. , A possible reason for the stabilization during this phase transition is the stronger Nb–O bonds. According to a recent study by Hu et al on the fundamental links between the spatial structure, electrochemical properties, and chemical composition of metal oxide cathodes, oxygen release is also a cause of surface phase changes and local stresses, which contribute to the formation of intergranular cracks . As Hu et al demonstrated in their study, our study shows a link between stronger oxygen binding (in our case via Nb–O bonds) and a reduced formation of intergranular cracks …”
Section: Resultssupporting
confidence: 70%
“…[27][28][29] Although the Li/Ni mixing ratio calculated by XRD refinement has uncertainty, the estimated Ni Li ratio seems comparable to previously reported values from NCM-based materials. [29][30][31] Detailed structural parameters and reliability factors obtained from Rietveld refinement are summarized in Table S1 (Supporting Information). A typical secondary particle morphology was observed in the scanning electron microscopy (SEM) images (Figure 1b).…”
Section: Structural/electrochemical Characterization Of Ncm622mentioning
confidence: 99%
“…Recently, electric vehicles have already become a reality around the world, so development of power sources, which guarantee their long driving ranges and safety is critically important. Among these power sources, advanced lithium ion batteries (LIBs) are the most appropriate ones for electrochemical propulsion, since they may provide the necessary high energy density, cycle life, stability, and reasonable safety [1][2][3][4][5][6][7][8][9][10][11]. The limiting factor of energy content in LIBs are the positive electrodes (cathodes) and their improvement is much more effective compared to other parts of batteries to get high energy density [12].…”
Section: Introductionmentioning
confidence: 99%